Philanthropy, Religiosity, and Private Giving: The Determinants of Charitable Giving and Religious Giving in Malaysia - Goh, Yee Hoon (2007)
The empirical literature on the economics of philanthropy and the economics of religion has predominantly focused on data from the developed countries. These studies have generally found that charitable giving and religious contributions by individuals are determined by several economic factors and sociodemographic variables, including price of giving, income level, age, gender, marital status, and educational attainment. Furthermore, most studies have only examined total charitable giving in general with no distinction by religious content. This study attempts to empirically investigate the determinants of religious and non-religious giving by Malaysians. Furthermore, this study also analyzes these two types of giving separately to examine the theoretical argument that only religious giving is influenced by belief in afterlife consumption and hence religious giving is fundamentally different from non-religious charitable giving. Overall, the findings of this study are broadly consistent with the results of previous research, albeit with some interesting distinctions. The results indicate that age, income level, and gender are statistically significant determinants of non-religious charitable giving, while religious giving is significant influenced by age, income level and marital status. While non-religious charitable giving is tax price elastic, religious giving appears to be inelastic with respect to tax price. As expected, the elasticity estimates indicate that both religious giving and non-religious charitable giving are inelastic with respect to income. Interestingly, there appears to be an age effect on the two with no evidence of a stronger age effect on religious giving than on non-religious giving. Notwithstanding this, taking the overall regression results as a whole, one can clearly discern that non-religious charitable giving is essentially different from religious giving.